Vanillin Affects Amyloid Aggregation and Non-Enzymatic Glycation in Human Insulin. Issue 1 (December 2017) - Iannuzzi, Clara; Borriello, Margherita; Irace, Gaetano; Cammarota, Marcella; Di Maro, Antimo; Sirangelo, Ivana
Abstract Curcumin is known for its anti-inflammatory, antioxidant and anticancer activity, as well as for its ability to interfere with amyloid aggregation and non-enzymatic glycation reaction, that makes it an attractive potential drug. However, curcumin therapeutic use is limited because of its low systemic bioavailability and chemical stability as it undergoes rapid hydrolysis in physiological conditions. Recently, much attention has been paid to the biological properties of curcumin degradation products as potential bioactive molecules. Between them, vanillin, a natural vanilla extract, is a stable degradation product of curcumin that could be responsible for mediating its beneficial effects. We have analyzed the effect of vanillin, in comparison with curcumin, in the amyloid aggregation process of insulin as well as its ability to prevent the formation of the advanced glycation end products (AGEs). Employing biophysical, biochemical and cell based assays, we show that vanillin and curcumin similarly affect insulin amyloid aggregation promoting the formation of harmless fibrils. Moreover, vanillin restrains AGE formation and protects from AGE-induced cytotoxicity. Our novel findings not only suggest that the main health benefits observed for curcumin can be ascribed to its degradation product vanillin, but also open new avenues for developing therapeutic applications of curcumin degradation products.